2012
DOI: 10.7314/apjcp.2012.13.4.1639
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Significance of Microsomal Prostaglandin Synthase-1 (mPGES-1) and Beclin-1 in the Development of Prostate Cancer

Abstract: The aim of this study was to investigate the expression and significance of microsomal prostaglandin synthase-1 (mPGES-1) and Beclin-1 in the development of prostate cancer (PCa). Immunohistochemistry was performed on paraffin-embedded sections with rabbit polyclonal against mPGES-1 and Beclin-1 in 40 PCa, 40 benign prostatic hyperplasia (BPH) and 10 normal prostate specimens for this purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 35 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…BECN1 has therefore been identified as a candidate tumor suppressor gene for ovarian cancer (6). Previous studies have revealed that the expression of Beclin-1 is downregulated in breast (7), prostate (8) and nasopharyngeal (9) carcinomas. Further studies have revealed that a loss of Beclin-1 expression results in reduced autophagy activity and increased tumorigenesis (10).…”
Section: Introductionmentioning
confidence: 99%
“…BECN1 has therefore been identified as a candidate tumor suppressor gene for ovarian cancer (6). Previous studies have revealed that the expression of Beclin-1 is downregulated in breast (7), prostate (8) and nasopharyngeal (9) carcinomas. Further studies have revealed that a loss of Beclin-1 expression results in reduced autophagy activity and increased tumorigenesis (10).…”
Section: Introductionmentioning
confidence: 99%
“…mPGES-1 is low in normal tissue and is induced in any inflammation. Studies have shown that it is overexpressed in a variety of human cancers, such as lung cancer [ 4 ], stomach cancer [ 5 ], colon cancer [ 6 ], prostate cancer [ 7 ], breast cancer [ 8 ], cervical cancer [ 9 ], pancreatic cancer [ 10 ], melanoma [ 11 ], squamous carcinoma of the head and neck [ 12 ], papillary carcinoma of the thyroid [ 13 ], and glioma [ 14 ]. Therefore, mPGES-1 has become an important target for the treatment of acute and chronic inflammatory diseases and cancers as shown in Supplementary Figure S1 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%